Atom‐Efficient Synthesis of Alkynylfluoroborates Using BF3‐Based Frustrated Lewis Pairs. Issue 45 (6th October 2016) - Iashin, Vladimir; Chernichenko, Konstantin; Pápai, Imre; Repo, Timo
Abstract: A sterically demanding amine, 1, 2, 2, 6, 6‐pentamethylpiperidine (PMP), forms a highly reactive Lewis acid–base pair with boron trifluoride. This pair reacts with terminal acetylenes to give the products of C(sp)−H borylation, previously unknown tri‐ and tetraalkynylboron compounds. Trialkynylfluoroborates can serve as surrogates of alkynyltrifluoroborates for C−C coupling reactions. Using aqueous NaOH, PMP can be recovered from its tetrafluoroborate salt, which is formed as a C−H borylation byproduct. Combining the discovered borylation reactivity with the PMP recovery provides a straightforward and atom‐efficient approach to synthetically useful alkynylfluoroborates. Abstract : C−H borylation : A simple aliphatic amine and BF3 complexes react with terminal acetylenes to give the C(sp)−H borylation products, previously unknown tri‐ and tetraalkynylboron derivatives. The amine, which is converted into the tetrafluoroborate salt during borylation, can be recovered by using aqueous NaOH.